An investigation on challenges experienced by open day secondary schools running within a conventional secondary school: a case of katoto, rumphi and chilumba secondary schools. - Munyimbili, Joseph W.C. (Mzuzu University, 2014)
The research sought to determine challenges that are faced open secondary schools running within conventional secondary schools. Open schools offer education to both youths and adults as an alternative for those who cannot access conventional secondary school The research used the case study design. Questionnaires were used as data collecting instruments. Records like teaching time tables, Malawi National Examination’s results for MSCE and learners’ progress books kept by administrators and teachers were also used. Oral interviews were also used in collecting data. To ensure representative samples, learners were sampled using stratified method, whereby they were divided into different classes and sex. Convenience sampling was used in selection of administrators from both the open and conventional schools. Open school students seemed not to have a real voice in the institutions where they were attending schools resulting into indiscipline reactions like stealing and vandalisms. There were no establishments of student prefect bodies to act as bridge between students and teachers. There were no establishment of structures by Government to ensure supervision in the running of open secondary schools. Findings also revealed that challenges are caused by neglecting the rules on admission. Rules stipulate that registration for any course should be based upon production of evidence of having passed the previous level of Government examinations. While open secondary students are also part of the main school, this research’s findings revealed that learners are denied access to library, transport, laboratory, night studies and entertainments facilities. This affected their grades in both Junior Certificate Examinations and the Malawi School Certificate Examinations. The research had financial and operational limitations. The impact of these limitations on the whole process were however, mitigated by the controls adopted by the researcher.